Historical and legal premises for modernization of Scientific personnel training system in Ukraine - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article analyzes the basic stages of the scientific personnel training system in independent Ukraine and the peculiarities of development of its regulatory and legal support. It deals with historical and legal features of the initiation, development and implementation of the legal provisions that provide institutional course of this process. The regulatory mechanisms of legislative acts are characterized determining the state policy for training of the highly qualified scientific and pedagogical staff, the basic tendencies in the developing of legal and regulatory frameworks, and directly linking to the qualitative improvement of this process. The genesis of the Higher Attestation Commission functions is investigated as a common state body that controls procedures for graduation and academic status conferment. The article pays attention to the consistent strengthening of its regulatory functions and increasing formalization in the process of preparation and defence of the research results by applicants. Historical and legal premises for modernization of the training system for highly qualified scientific and pedagogical staff in Ukraine are determined. The conclusion is grounded that the national training system for highly qualified scientific and pedagogical staff and its regulatory and legal support passed in its development the evolutionary path from institutional functions of the state on the system of regulation of procedures for certification and monitoring of the implementation of European standards in the scientific and educational fields that determine the formation and maintenance of the knowledge society as a key function of the state in this process. It is emphasized that the success in the process of introducing of European standards for scientific personnel training is defined by both efficiency of new legal rules and taking into account the national experience. It is determined that today an active formation of fully functional legal framework for implementation of European principles of doctoral programs’ organization is being realized and this process has historical and legal conditionality.